Prosthetic Rehabilitation of Congenitally Missing Digits - Jaidev, Reetika; Bansal, Ashish; Shadakshari, Shivamurthy; Nandeeshwar, DB (Journal of Orofacial Research, 2013)
Complete or partial fingers are the most commonly encountered forms of partial hand losses. Though finger amputations are commonly due to traumatic injuries, digit loss may also be attributed to congenital malformations and diseases. Irrespective of the etiology, digit loss has a considerable functional, psychological and social impact on an individual. This clinical report describes the fabrication of silicone glove type finger prosthesis for a 36 years old male patient with congenitally missing index and middle finger in the left hand. The prosthesis offered psychological, functional and rehabilitative advantages for the patient.